Factors associated with the development of self-harm amongst a socio-economically deprived cohort of adolescents in Santiago, Chile - Spears, Melissa; Montgomery, Alan A.; Gunnell, David; Araya, Ricardo (Social Psychiatry and Psychiatric Epidemiology, 2014)
Purpose Studies carried out in the West indicate that the incidence of self-harm (SH) is particularly high amongst adolescents, but few studies have investigated its incidence and aetiology in low-income countries. The purpose of this study was to investigate risk factors associated with new onset episodes of SH, amongst Chilean adolescents from low socio-economic backgrounds. Methods Prospective cohort study nested within a cluster randomised controlled trial. A 6-month follow-up for 2,042 adolescents, median age 14 years, from socio-economically deprived areas of Santiago, Chile. Results The lifetime prevalence of SH was 23 %. The incidence rate of SH at 6 months was 14 % amongst those reporting no SH at baseline. In multivariable analyses, risk factors for incident SH include depressive symptoms, suicidal thoughts, poor problem-solving skills and cannabis misuse. Conclusions The prevalence and incidence of SH in this socio-economically deprived sample differed highly according to gender. Poor problem-solving skills, suicidal thoughts, and cannabis misuse were associated with onset of SH.